Of Hairy Kings and Saintly Slaves: an Ethiopian travelogue - Ramos, M. J. (2018)
Travel drawing is more than a record or register of attendance ('been there, seen that'): it holds invisibly within itself the remnant of a look, the hint of a memory and a trace of an osmosis of feelings between the sketcher and the person or objects sketched. Less intrusive than using a camera, drawing comprises a less imperialist, more benign way of researching: the sketchbook becomes a means of communication between the observer and the travelled world, rendering him/her more human to those around. This book is a journey through the Ethiopian Central Highlands, in pursuit of historical legends about the power struggles surrounding the arrival of the first Europeans in the mid-sixteenth century. It includes excerpts from an ethnographic diary, recording encounters with the priests, elders and historians who act as custodians of the Amhara oral tradition. Their tales are interwoven with improvised drawings, and this informality of structure retains the immediacy of a discovery of Ethiopia. It also suggests the potential for drawing to play a more active part in anthropological production, as a means of creating new narratives and expositional forms in ethnography, bringing it closer to travel writing or the graphic novel.